Investigating lipid signaling in rat hippocampal slices with patch-clamp tight seal whole cell recording technique - Genç, Özgür. (Thesis (M.S.)-Bogazici University. Institute of Biomedical Engineering, 2007., 2007)
Ceramide, besides its structural role in cell membrane as a sphingolipid, has essential roles in apoptosis, cell growth and di erentiation. In this study, the e ect of C2-ceramide (10 μM) application on whole cell currents recorded by patch-clamp technique from cell body of hippocampal CA1 pyramidal neurons was investigated. Evoked post-synaptic currents were recorded with low frequency (0.1 Hz) stimulation of Scha er collateral. It was observed that ceramide application resulted with depression among the NMDA currents. On the other hand, there was not any signi cant in uence on non-NMDA currents. The role of C2-ceramide which leads to the depression on the NMDA currents showed that sphingolipids have an e ect directly on the cell membrane, besides their roles as secondary messengers inside the cell.|Keywords: C2-ceramide, hippocampal synaptic currents, NMDA and non-NMDA currents, patch-clamp tight seal whole cell technique.
Keywords: Hippocampus (Brain); Methyl aspartate.